INVESTIGATION OF FACTORS INFLUENCING TUBERCULOSIS DEVELOPMENT IN CHILDREN ACCORDING TO TUBERCULOSIS CONTACT HISTORY - Khakimov Abdulatif Abduvali o‘g‘li; Djurabaeva Mukhabbat Khusanovna (TADQIQOTLAR, 2026)
Background: Tuberculosis (TB) remains a significant global health concern, especially  among  children.  Understanding  the  risk  factors  associated  with  TB development  in  pediatric  populations  is  crucial  for  effective  prevention  and management. Objective: This study aims to compare risk factors between children who have direct contact with TB patients and those who do not, with the goal of identifying key determinants of TB susceptibility. Methods: We conducted a analysis of pediatric TB cases from medical records. Participants were divided into two groups: Group A (children with direct TB exposure) and  Group  B  (children  without  direct  TB  exposure).  Demographic,  clinical,  and environmental variables were assessed. Results: Preliminary findings indicate that children with direct contact with TB patients  are  at  higher  risk  of  developing  TB.  Key  risk  factors  include:  Household Exposure  - Children  living  in  close  proximity  to  active  TB  cases  face  increased transmission risk; Malnutrition - Poor nutritional status weakens the immune system, making  children  more  susceptible  to  TB  infection;  Crowded  Living  Conditions - Overcrowded households facilitate TB transmission. Conclusion: Our study underscores the importance of targeted interventions for high-risk pediatric populations. Early case detection, nutritional support, and infection control measures are essential in reducing TB incidence among children.